Highly Efficient Room‐Temperature Phosphorescence Based on Single‐Benzene Structure Molecules and Photoactivated Luminescence with Afterglow. (19th February 2021) - Ma, Liangwei; Sun, Siyu; Ding, Bingbing; Ma, Xiang; Tian, He
Abstract: Recently, a remarkable advance has been made for metal‐free room‐temperature phosphorescence (RTP) crystals with high phosphorescence quantum yield. However, amorphous, especially heavy‐atom‐free, RTP materials still suffer from low quantum yield due to the transition‐forbidden character of phosphorescence and the relatively poor suppression of nonradiative transition in amorphous materials. In this study, a series of single‐benzene structure‐based high intersystem crossing yield phosphor is obtained. After embedding into polyvinyl alcohol matrix, all these phosphor exhibits efficient phosphorescence emission (ФP, up to 44.0%). Besides, photo‐switchable phosphorescence emission can be obtained by doping these molecules into a polymethyl methacrylate (PMMA) matrix. The phosphorescence can be gradually switched on by consuming the residual oxygen in the PMMA matrix under continuous UV light irradiation. Furthermore, the phosphorescence will be spontaneously switched off under ambient conditions. Taking advantage of the photoactivation character, this material has potential in information storage and anti‐counterfeiting. Abstract : A series of polyvinyl alcohol thin films with high intersystem crossing yields and phosphorescence quantum yields (up to 44.0%) are prepared from newly synthesized single‐benzene based, heavy‐atom‐free derivatives. Furthermore, an information writing‐erasing‐rewriting film and anti‐counterfeiting label are established by using the poor oxygen barrier properties of polymethyl methacrylate and the photo‐induced oxygen scavenge process.